2007
DOI: 10.1111/j.1442-9071.2007.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal haze after combined riboflavin‐UVA corneal collagen cross‐linking in keratoconus: in vivo confocal microscopic evaluation

Abstract: The technique of corneal collagen cross-linking consists of photopolymerization of stromal fibres by the combined action of a photosensitizing substance (riboflavin or vitamin B2) and ultraviolet light from a solid state UVA source. Photopolymerization increases the rigidity of corneal collagen and its resistance to keratectasia. In this report we present two cases, studied through in vivo confocal microscopy, with stage III keratoconus that developed stromal haze after the cross-linking treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
2
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 5 publications
8
135
2
13
Order By: Relevance
“…Despite the overall enthusiasm for offering CXL to KC patients, adverse events have been incompletely assessed in the literature. 13,14 Koller et al 9 reported an overall adverse event rate of 2.9% in 105 eyes, and identified age Z35 years as the most important independent risk factor for adverse events after CXL. However, this findings needs to be interpreted cautiously, because, given the figures provided in the paper, the estimated number of eyes in patients aged 435 years enrolled in the Koller study was only 15 with 2 failures, corresponding to a mean probability of 0.13 and a binomial exact 95% CI of 0.02-0.40.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the overall enthusiasm for offering CXL to KC patients, adverse events have been incompletely assessed in the literature. 13,14 Koller et al 9 reported an overall adverse event rate of 2.9% in 105 eyes, and identified age Z35 years as the most important independent risk factor for adverse events after CXL. However, this findings needs to be interpreted cautiously, because, given the figures provided in the paper, the estimated number of eyes in patients aged 435 years enrolled in the Koller study was only 15 with 2 failures, corresponding to a mean probability of 0.13 and a binomial exact 95% CI of 0.02-0.40.…”
Section: Resultsmentioning
confidence: 99%
“…All trials have indicated a time-dependence of the effects of CXL, both in terms of transient haze 54 and edema in the early stages, as well as in refractive outcome, which seems to improve over the first year or more following treatment 26,30,31,[51][52] .…”
Section: Effect Of the Treatment On Cornea Claritymentioning
confidence: 99%
“…Despite the fact that no sight-threatening complications were recorded in the large prospective studies, there are some sporadic reports of stromal haze resistant to topical steroid treatment (Mazzota et al, 2007), diffuse lamellar keratitis in post-LASIK ectasia, herpetic keratitis and iritis , Acanthamoeba keratitis with corneal perforation (Rama et al, 2009), and microbial keratitis (Pollhammer & Cursiefen, 2009;Zamora & Males, 2009). Other potential complications include delay in reepithelization, sterile infiltrates, potential for induction of herpes simples virus and dendritic ulcer, and ocular surface disorders and tear dysfunction (Corkin, 2009).…”
Section: Treatmentmentioning
confidence: 99%